Pengaruh Aromaterapi Lavender, Relaksasi Otot Progresif dan Guided Imagery terhadap Kecemasan Pasien Pre Operatif - Handayani, Ririn Sri; Rahmayati, El (Jurnal Kesehatan, 2018)
An anxious condition of the patient will affect the function of the body before surgery. High anxiety can affect the physiological function of the body which is characterized by an increase in pulse and respiration frequencies, a shift in blood pressure and temperature, relaxation of smooth muscles in the bladder and intestines, cold and moist skin, increased respiration, pupillary dilation, and dry mouth. This condition is very dangerous for the patient's condition so that an operation can be canceled or postponed. Other consequences, the length of patient care will be longer and cause financial problems. The aim of the study was to determine the effectiveness of lavender aromatherapy, progressive relaxation, and guided imagery to reduce preoperative anxiety in patients. The research design used was Quasi-experimental with Pre post-test design or one group before and after. The study population was adult patients who would undergo elective surgery at dr. H. Abdul Moeloek Lampung Province. The large calculation of samples taken using the Sample Size Calculator For Designing Clinical Research for one group before after study for the paired t-test statistical test. By setting Alpha 0.01, Betha 0,100, Effect Size 0,500 and Standard Deviation 1.00 so that the number of samples used is equal to 60 people. The sampling technique uses simple random sampling method. The results of this study concluded that lavender aromatherapy, progressive muscle relaxation, and guided imagery were effective in reducing preoperative anxiety (mean score before intervention 7.67 (SD 7.890), score after intervention 4.05 (SD 5.806)) with ρ value 0.000. Researchers suggest that lavender aromatherapy, progressive relaxation, and guided imagery can be used as standard interventions in preoperative anxiety diagnosis of patients' anxiety by nurses, this therapy should be done several times until the patient will enter the operating room and this therapy can be taught to nursing students as an action to overcome preoperative anxiety.